(untitled) (Journal of Libya for geographical studies, 2023)
The study aims at assessing the mechanism followed to manage the dangerous, medical, hard wastes in Misurata Medical Centre (MMC). This is done according to the recommendations of the WHO. The study, moreover; aims at determining the way such wastes are treated, checking the suitability of that treatment in comparison with the output wastes. To obtain the results, descriptive method is used to describe waste management within various sections of the center. A comparative method is utilized to find out similarities and differences between what is done in the hospital versus what is globally agreed on. And finally, the waste average of some sections is summed quantitivly. In conclusion, the results revealed that the medical staff is unqualified as well as unaware enough to deal with such kind of wastes. The hospital lacks the special bags and containers used for keeping away wastes. It is also found that though infectious wastes are treated by autoclaving process, the shredder size is too small.